Sunn hemp reinforced poly(lactic acid) green composites: Controlled biodegradation and improved fracture toughness through interlocking mechanism - Raj H.; Choudhury A.M.; Tripathi S.; Bauri S.; Mandal S.S.; Prakash R.; Tiwari S.; Layek R.K.; Maiti P. (My University, 2025)
Over the past few decades, great attention has been paid to the development of green composites due to rising pollution and depletion of natural resources. Polymer composites cater the need for high-strength sustainable materials. Poly(lactic acid) (PLA) is one of the synthetic biopolymers, produced in large scale and exhibits sufficient mechanical properties. Natural fibres are present abundantly across the globe and can be used as natural reinforcement. Sunn hemp is one of the widely grown fibrous crops known for its high-strength fibres for rope production. This study is carried out to establish the Sunn hemp fibre as reinforcement for PLA. PLA/Sunn hemp green composites were developed via compression moulding with different filler contents. The mechanical, spectroscopic, thermal, and biodegradation studies of the composites have been performed. The addition of sun hemp fibers increases tensile strength by more than 100 % from 44 MPa for PLA to 95 MPa for composite. Toughness of PLA has also been increased by 87 %. Thermomechanical studies indicate storage modulus has increased by 59 %. Fibers have also enhanced biodegradation rate of PLA significantly. These studies show that prepared composites show better mechanical, thermal performance and unique relaxation behaviour than that of pure PLA. The rheological, antibacterial and biodegradation studies indicate its green behaviour and easy processing for its application in biomedical arena. © 2024